Entrepreneurial Competence, Market Orientation, and Digital Literacy Impact on MSME Culinary Marketing Performance in Indonesia - Ramdan, Asep Muhamad; Siwiyanti, Leonita; Komariah, Kokom; Nurmillah, Risma; Ramdhany, Muhamad Arief (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are key drivers of economic growth, including in Sukabumi Regency, Indonesia, yet they face challenges in sustaining growth and enhancing competitiveness. This study examines the interplay of entrepreneurial competence, market orientation, and digital literacy in influencing MSME marketing performance. Employing a quantitative design, data were gathered from 370 MSME entrepreneurs via survey questionnaires. The analysis applied descriptive statistics and Structural Equation Modeling using the Partial Least Square (SEM-PLS) method to test hypotheses and explore relationships among variables. Findings reveal that entrepreneurial competence significantly affects marketing performance, both directly and indirectly through market orientation. Digital literacy strengthens the positive relationship between entrepreneurial competence and marketing performance. However, contrary to expectations, digital literacy does not significantly moderate the effect of market orientation on marketing performance. These results underscore the importance of entrepreneurial skills and digital capabilities in improving marketing outcomes. The study offers valuable implications for policymakers and support institutions to develop targeted programs that enhance entrepreneurial competence and digital literacy among MSMEs. Its originality lies in the integrated analysis of mediating and moderating effects, providing deeper insights into the determinants of marketing success in the MSME culinary sector.